Frenzied monkeys: Imaginaries of Subhuman Slavery in the Literary Racism of José de la Cuadra - Martínez-Magdalena, Santiago (Revista de Antropología Social, 2026)
Starting from a Latin American literary corpus that explores the relationships of humanity and rebellion of monkeys, we focus on the specific development practiced by the Ecuadorian storyteller José de la Cuadra (1903-1941). As the monkey appears as a trained slave, whose miserable life unfolds between energetic and sexual slavery, and object subhumanity, we aim to undertake an anthropological approach to this production, all within the context of the Latin American Primatological Park.
Keywords: humanity; animality; subhumanity; José de la Cuadra